2015
DOI: 10.4142/jvs.2015.16.3.357
|View full text |Cite
|
Sign up to set email alerts
|

Tissue Doppler and strain imaging of left ventricle in Beagle dogs with iatrogenic hypercortisolism

Abstract: Changes in radial and longitudinal left ventricular (LV) function were investigated in beagles with iatrogenic hypercortisolism. A total of 11 normal dogs were used, and 2 mg/kg prednisone was administered per oral q12 h for 28 days to 7 out of 11 dogs to induce iatrogenic hypercortisolism. Body weight, blood pressure, conventional echocardiography and tissue Doppler imaging (TDI) of normal and iatrogenic hypercortisolism groups were conducted. The myocardial wall velocity of the LV was measured using color TD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 26 publications
(38 reference statements)
1
6
0
Order By: Relevance
“…LVH and fibrosis are also caused by systemic hypertension, a common complication in CS [ 2 , 15 ]. None of the conventional echocardiographic results correlated with SBP, which is consistent with previous reports of no relationship between LVFW thickness and systolic blood pressure in canine CS patients [ 22 , 44 ].…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…LVH and fibrosis are also caused by systemic hypertension, a common complication in CS [ 2 , 15 ]. None of the conventional echocardiographic results correlated with SBP, which is consistent with previous reports of no relationship between LVFW thickness and systolic blood pressure in canine CS patients [ 22 , 44 ].…”
Section: Discussionsupporting
confidence: 90%
“…Furthermore, cardiomyocyte hypertrophy and increased myocardial fibers have been reported as histopathological changes in the heart [ 25 , 30 , 43 ]. Recently, in veterinary medicine, LVH and DD have been reported in dogs with CS and those receiving high-dose prednisolone [ 9 , 22 , 44 ]. To our knowledge, current experimental studies on dogs are short-term evaluations [ 22 , 32 , 45 ] that report no obvious histopathological myocardial changes [ 22 ].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The model used for this study is that for cardiovascular research. A previous report examined a model in which dogs were administered a high dose synthetic corticosteroid at 2 mg/kg every 12 h for 28 days, which showed changes in echocardiographic cardiac morphology and function; however, histological changes were not observed [18]. Past studies have suggested that chronic hypercortisolism can affect cardiac function and morphology [19,20].…”
Section: Animalsmentioning
confidence: 99%
“…Specifically, hypertrophy of cardiomyocytes and an increase in the cardiac fiber count were reported as histopathological changes ( Sugihara et al , 1992 ). Recently, left ventricular hypertrophy and cardiac dysfunction had been reported in dogs with HAC and in those experimentally treated with high-dose prednisolone ( Chen et al , 2014 ; Oui et al , 2015 ; Takano et al , 2015 ; Tanaka et al , 2021 ). A histopathological study of dogs showed no apparent change in the myocardium when a 2 mg/kg prednisolone dose was administered every 12 hours for 28 days ( Oui et al , 2015 ).…”
Section: Introductionmentioning
confidence: 99%